„Pociągający” urok odległego świata – wybrane motywy w powieściach „Córka pastora” i „Żona pastora” fińskiego prozaika Juhaniego Aho - Mrozewicz, Bolesław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2019)
This article shows the issues of the place and the social role of the women in Finland of on the basis of the two Finnish classical, realistic 19th century novels: Pastor’s daughter and Pastor’s wife. Juhani Aho joins the discussion through his literary output. Being a pastor’s son, he chooses the characters for his deep analysis from his social group. In the latter one, Aho is referring to psychological trend emerging in Finland. The plot of both novels is set in the group of Finnish intelligence that, on the one hand, is represented by pastors from the small village parishes and, on the other hand, by the theology student from Helsinki. His stay in pastor’s house in the country and his unconventional behaviour can ruin the social order, which used to be accepted as the norm. The author focuses on the figure of a woman – the daughter, who is the eponymous character, and afterwards on the pastor’s wife, who is restricted by etiquette, feels the deep sorrow of her existence and attempts to compensate for her life in the pastor’s house by building her deeply hidden inner world. This world of idealized romantic dreams and unfulfilled desire to live in spiritually richer dimension causes –due to the reality around her –her permanent state of depression and frustration –in both emotional and social aspects. She is unable to change anything in her life, though the fate in the form of a student seems to offer her the chance.